Performance of ESG versus Shariah compliant firms in Malaysia. A conceptual framework - Sheikh Idris, Moizer; Haron, Razali; Che Embi, Nor Azizan; Hamdan, Hamdino (2017)
Shariah screening is a well-established concept in the Malaysian Equity Market; in fact Malaysia is considered one of the global leaders of Shariah compliant equity market. A new drive for the adoption of sustainable investment has materialized in Malaysia, through the introduction of Environmental, Social, and Governance (ESG) compliance index (FTSE4GOOD) in 2014. Shariah compliant investment and ESG has a common role of promoting responsible investing. However, there has been a lack of transfer between ESG & Shariah screening factors. Therefore, the aim of this paper is to investigate the available literature through content analysis technique, to identify the effect of ESG compliance on firm performance, and to determine the factors affecting firm performance. Thus, by understanding the importance of ESG towards firm’s performance, this will enable a smoother transfer between ESG and Shariah screening principles within the Malaysian equity market. Among the main factors that affect firm performance represented by profitability are firm’s size, age, leverage, capital structure, and liquidity.